Analisis Gaya Mengajar Klasik Terhadap Minat Belajar Siswa pada Mata Pelajaran Matematika Kelas V SD Negeri 1 Selanegara - Masruhah, Umi; Febriyani, Shoimatun; Azizah, Amalia Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the implementation of classical teaching styles on the learning interest of fifth-grade students in Mathematics at SD Negeri 1 Selanegara. The background of this research is the low interest in learning among students, characterized by passive learning participation and a lack of motivation in following lessons. This study uses a qualitative approach with 20 fifth-grade students as subjects. Data was collected through interviews, observations, and document studies. The instruments used include interview guides, observation sheets, and daily activity journals. The data analysis technique employs qualitative descriptive analysis. The research findings indicate that the classical teaching style is still predominantly used by fifth-grade teachers. Several factors underlying the use of this teaching style include: the absence of mandatory lesson planning or teaching modules in the Merdeka Curriculum, limited teaching time, the teachers' lack of ability in utilizing teaching aids and technology, a heavy administrative burden, and limited facilities in schools. The use of the classical teaching style impacts students' low interest in learning, as seen from their lack of active participation and motivation in Math classes.